The Effect of Price Earning Ratio, Return O Equity, Debt to Equity Ratio, Firm Size, and Dividend Payout Ratio to the Stock Returns on Banks Listed in LQ45 Index 2015-2020 - Ayu Kartika; Lies Handrijaningsih; Septi Mariani TR; Anisah Anisah (Ilomata International Journal of Tax and Accounting, 2022)
The capital market in Indonesia is currently experiencing very rapid development from year to year, as evidenced by the increasing number of public companies every year. Banking is one of the sub-sectors included in the LQ45 index with its average share having the highest market capitalization among other sub-sectors. The development of the capital market in Indonesia, including the banking sub-sector is inseparable from the supporting factors are internal factors as seen from the company's financial ratios. This study aims to determine the influence of price earning ratio, return on equity, debt to equity ratio, firm size, and dividend payout ratio on stock returns in banks listed on the LQ45 index for the period 2015-2020. The data collection method used in this study is the documentation method. The data used is secondary data, the determination of the sample in this study was carried out by purposive sampling method. The data in this study was processed using SPSS Application. The analysis tools used are, Descriptive Statistical Analysis, Classic Assumption Test, Multiple Linear Regression, T Test, F Test, and Determination Coefficient. The results of this study show that the price earning ratio, return on equity, debt to equity ratio, firm size, and dividend payout ratio affect stock returns simultaneously. Partially, the price earning ratio, return on equity, and debt to equity ratio affect stock returns, meanwhile firm size and dividend payout ratio have no effect on stock returns